Analysis of Marketing Strategy in Increasing Sales of Ibu Uun Spicy Noodles in West Jakarta - Novalia Talebong; Dito Aditia Darma Nasution (Basic and Applied Accounting Research Journal, 2022)
The purpose of this study is to find out the strategy in marketing Ibu Uun's Spicy Noodles in boosting sales. This qualitative and descriptive research approach is used. Essential and optional information is the type and source of information used, as well as the strategy for selecting information as a meeting and perception. Data were analyzed using descriptive analysis which refers to the 4P Marketing Mix (Product, Price, Place, Promotion). Based on the findings of the investigation, Ibu Uun's Spicy Noodles implemented a product strategy to boost sales. There are various levels of choice (level 1 to 3). Pricing strategy that allows for reasonable prices. Placement strategy, choosing a location that is comfortable and easy to reach. Initially, the promotion strategy was carried out through face-to-face sales, and then implemented through social media. Customers who are happy with the products and services provided also spread the word of mouth. It turned out that the implementation of this strategy had a significant impact on Ibu Uun's sales of Spicy Noodles, which have always increased since the store opened.